Visual Function of Tuberculosis Patients Receiving Ethambutol in Kassala, Sudan: A Cross-Sectional Study - Mohammed Ibrahem Obied Babiker; Hana Khalid Salam Ahmed; Rwanza Stayed Mohammed Sayed (American Journal of Medicine and Health Care, 2026)
Ethambutol is a first‑line antituberculosis drug whose dose‑dependent optic neuropathy may lead to irreversible vision loss if undetected. However, real-world data on its ocular impact from Sudan remain scarce, despite a high tuberculosis burden and prevalent malnutrition. To describe the visual function findings (visual acuity, color vision, pupillary reactions, intraocular pressure, and fundoscopic appearance) in tuberculosis patients receiving ethambutol-containing regimens. A hospital‑based cross-sectional study was conducted from July to December 2024. Seventy‑three adult TB patients receiving ethambutol without pre-existing vision problems were interviewed, and ocular assessments, including visual acuity, Ishihara color vision, pupil reactions, intraocular pressure, and direct fundoscopy, were performed by ophthalmologists. Data were analyzed descriptively. Most participants were 25–34 years old (42.5 %) and male (53.4 %). After commencing ethambutol, 13.7 % reported subjective vision changes, and symptoms suggestive of ocular toxicity (e.g., blurred central vision, difficulty reading) were present in 15.1 %. Despite this, 94.5 % of right eyes and 95.9 % of left eyes maintained 6/6 visual acuity, and abnormal color vision was documented in only 1.4 % of eyes. Fundoscopy revealed optic‑nerve or retinal abnormalities in 1.7 % of patients. Notably, no participant reported any chronic comorbidity, and 82.2% consumed vitamin-rich or diverse diets. Clinically significant ethambutol‑induced ocular toxicity was infrequent in this Sudanese cohort, possibly due to the absence of comorbidities and favorable nutritional status.